Effect of Growth Regulators and Methods of Application on Growth, Fruit and Seed Yield in Paprika Chilli (Capsicum annuum L.) cv. Kt-Pl-19 - SHANTAPPA TIRAKANNANAVAR; A.M. SHAMSHEER AHMED; P.M. MUNIKRISHNAPPA; MUKESH, L. CHAVAN; A.B. MASTIHOLI (Seed Research, 2026)
Effect of growth regulators viz., NAA (40 ppm), GA, (50 ppm), CCC (500 ppm) and 2,4-D (5 ppm) and methods of application on growth, fruit and seed yield in paprika chilli cv. Kt-Pl-19 was studied during kharif 2006-07. Among the growth regulators, NAA @ 40 ppm was found most effective for higher plant height at 30, 60and 90 days after transplanting, more number of fruits per plant (25.20), 1000 seed weight (5.92g), fruit yield per hectare (924.8kg), seed yield per plant (12.77 g) and per hectare (371.23 kg).Between the methods of application, application of growth regulators at flower bud initiation stage recorded the highest plant height at 60 and 90 days after transplanting, more number of fruits per plant (22.97), 1000 seed weight (5.81 g), fruit yield per hectare (924.8kg), seed weight per fruit (2.41g), seed yield per plant (12.02 g) and per hectare (353.88 kg). Applications of NAA (40 ppm) or GA3 (50 ppm) at flower bud initiation stage were most effective for higher fruit and seed yield in paprika chilli.